Experimental research to develop simple mathematical imagination in preschool children through music - Byambajav, Myagmar; Banzragch, Narantsetseg (Lavai - International Journal of Education, 2022)
The study presents an educational activity plan that integrates teaching Music with Mathematics and organizes it in a unified way that appeals to children and is tested over a period of three months. The planning and organization of the training in a unified way affect the development of the child's memory, attention, and brain. Not only does it develop real and abstract thinking, free and creative thinking, but also serves as a preparatory basis for moving to the next level of training. The research which used experimental methods and techniques included fifteen children from a private kindergarten in Ulaanbaatar. The performance of the tasks on number frequency and rhythm, spatial and musical movements, number sequence, and volume was twenty percent higher after integrated Music and Mathematics training, indicating that the capacity to learn Mathematics through Music has been improved. It has been observed that Music and Mathematics training can be conducted in an integrated way and be more effective when children perform exercises on number sequences, regularity, spatial relations, etc. while listening to the rhythm of music, singing, performing musical movements, or playing simple musical instruments. Хөгжмөөр дамжуулан сургуулийн өмнөх насны хүүхдийн математик төсөөллийг хөгжүүлэх туршилт судалгаа Хураангуй Тус судалгаагаар хөгжмийг математиктай холбон, хүүхдийн сонирхлыг татахуйц нэгдмэл хэлбэрээр зохион байгуулж, нэг улирал буюу гурван сарын хугацаанд туршсан сургалтын үйл ажиллагааны төлөвлөгөөг танилцуулж байна. Сургалтыг нэгдмэл төлөвлөснөөр хүүхдийн ой тогтоолт, анхаарал, тархины хөгжилд онцгой нөлөөлж бодит, хийсвэрлэн сэтгэхүй, чөлөөт, бүтээлч сэтгэлгээ нь хөгждөг төдийгүй дараагийн шатны сургалтад шилжих бэлтгэл суурь нь болж өгдөг. Судалгаанд Улаанбаатар хотын хувийн цэцэрлэгт суралцаж буй 15 хүүхэд хамрагдсан ба туршилт судалгааны аргыг ашигласан. Хөгжим математикийн нэгдмэл сургалтаар тооны давтамж ба хэмнэл, орон зай ба хөгжимт хөдөлгөөн, тооны дараалал-өндөрлөг, цомнол гэсэн даалгаврын гүйцэтгэл нь гарааны үнэлгээнээс 20 хувиар илүү үзүүлэлттэй гарсан нь хөгжмөөр дамжуулан математикт суралцах чадвар нь илүү байгааг харуулж байна. Хүүхэд хөгжмийн хэмнэлийг мэдэрч дуулах, хөгжимт хөдөлгөөн хийх, энгийн хөгжмийн зэмсгээр тоглох явцдаа тооны дараалал, зүй тогтол, орон зайг баримжаалах зэрэг дасгал даалгаврыг гүйцэтгэсэн нь хөгжим математикийн сургалт нэгдмэл байдлаар явагдах боломжтой бөгөөд илүү үр дүнтэй нь ажиглагдлаа. Түлхүүр үг: Хүүхэд, нэгдмэл сургалт, хөгжим математик